P.083 Early and 30-day clinical and neuropsychological effects of iatrogenic brain infarcts in the ENACT randomized-controlled trial. (November 2021) - Ganesh, A; Ospel, JM; Wilson, AT; Goyal, M; Tymianski, M; Hill, MD
Abstract : Background: Small brain infarcts are often seen on diffusion-weighted MRI(DWI) following surgical/endovascular procedures. Little is known about their clinical effects. We examined the association of iatrogenic infarcts with outcomes in the ENACT(Evaluating Neuroprotection in Aneurysm Coiling Therapy) trial of nerinetide in endovascular aneurysm repair. Methods: In this post-hoc analysis, we used multi-variable models to evaluate the association of presence/number of DWI iatrogenic infarcts with NIHSS(National Institutes of Health Stroke Scale), mRS(modified Rankin Scale), and cognitive/neuropsychological scores(30-minute battery) at 1-4 and 30-days post-procedure. We also related infarct number to a Z-score-derived composite outcome score(quantile regression). Results: Among 185 patients(median age:56, IQR:50-64), 124(67.0%) had iatrogenic infarcts(median:4, IQR:2-10.5). Nerinetide resulted in fewer infarcts. Patients with infarcts had lower Mini-Mental State Exam(MMSE) scores at 2-4 days(median:28 vs 29, adjusted-coefficient[acoef] per additional infarct:-1.11, 95%CI:-1.88 to -0.34, p=0.005). Infarct number was associated with worse day-1 NIHSS(aOR for NIHSS≥1:1.07, 1.02-1.12, p=0.009), day 2-4 mRS(adjusted common odds-ratio[aOR]:1.05, 1.01-1.09, p=0.005) and MMSE(acoef:-0.07, -0.13 to -0.003, p=0.040), 30-day mRS(aOR:1.04, 1.01-1.07, p=0.016) and Hopkins Verbal Learning Test scores(acoef:-0.21, -0.39 to -0.03, p=0.020), as well as worse composite scores at 1-4 and 30-days(acoef:-0.09, -0.15 to -0.03, p=0.006). Conclusions: Iatrogenic infarcts were associated with subtle differences in post-procedural(1-4 days) and 30-day outcomes in this middle-aged cohort. Future studies should use batteries of similar/greater granularity to validate optimal measures for short- versus long-term manifestations.